2014
DOI: 10.1021/cn5002182
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric Agents Derived from the Functionalized Amino Acid, Lacosamide, and the α-Aminoamide, Safinamide: Evaluation of Their Inhibitory Actions on Voltage-Gated Sodium Channels, and Antiseizure and Antinociception Activities and Comparison with Lacosamide and Safinamide

Abstract: The functionalized amino acid, lacosamide ((R)-2), and the α-aminoamide, safinamide ((S)-3), are neurological agents that have been extensively investigated and have displayed potent anticonvulsant activities in seizure models. Both compounds have been reported to modulate voltage-gated sodium channel activity. We have prepared a series of chimeric compounds, (R)-7–(R)-10, by merging key structural units in these two clinical agents, and then compared their activities with (R)-2 and (S)-3. Compounds were asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 47 publications
2
19
0
1
Order By: Relevance
“…We have reported on a novel series of chimeric compounds, ( R )- A , 810 derived from the merger of key structural units (Fig. 1B, C) present in the functionalized amino acid (FAA), lacosamide 11 (( R )- N -benzyl 2- N -acetamido-3-methoxypropionamide, ( R )- 1 ) and the α-aminoamide (AAA), safinamide 12,13 (( S )-2-(4′-((3″-fluoro)benzyloxy)benzyl)aminopropionamide, ( S )- 2 ).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…We have reported on a novel series of chimeric compounds, ( R )- A , 810 derived from the merger of key structural units (Fig. 1B, C) present in the functionalized amino acid (FAA), lacosamide 11 (( R )- N -benzyl 2- N -acetamido-3-methoxypropionamide, ( R )- 1 ) and the α-aminoamide (AAA), safinamide 12,13 (( S )-2-(4′-((3″-fluoro)benzyloxy)benzyl)aminopropionamide, ( S )- 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…We demonstrated that select ( R )- A compounds displayed potent anticonvulsant activities in the maximal electroshock 18 (MES) and the 6-Hz psychomotor 19 seizure assays in rodents. 810 The anticonvulsant activities of ( R )- A have been attributed, in part, to their actions on voltage-gated sodium channel (VGSC) properties. 9,10,20 Chimeric compounds ( R )- A potently transitioned VGSCs to the slow-inactivated state and in some cases, affected fast inactivation processes and inhibited Na + currents in a frequency (use)-dependent fashion.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations